2003
DOI: 10.1002/macp.200390108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure, Crystallinity, and Morphology of Uncompatibilized and Compatibilized Blends of Polyethylene/Nylon 12

Abstract: The present study is aimed at investigating differences in molecular structure, crystallinity, and morphology between uncompatibilized and compatibilized blends of high‐density polyethylene (HDPE) and Nylon 12 by using Fourier‐transform (FT) Raman spectroscopy, wide‐angle X‐ray diffraction (WAXD), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). Uncompatibilized and compatibilized blends of HDPE/Nylon 12 with a Nylon 12 content ranging from 10 to 90 wt.‐% with an increment of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…7 Li et al reported that PP components crystallized isothermally are immiscible with HDPE and LDPE and are miscible with LLDPE. 14 The purpose of the present study is to investigate the molecular structure, crystallinity, and morphology of the three kinds of PE/PP blends, HDPE/PP, LLDPE/PP, and MEPE/PP by using Raman spectroscopy, [19][20][21][22][23][24][25] Raman mapping, 26 scanning electron microscopy (SEM), 24,25 WAXD, 23,27 and DSC. 25,27 Raman mapping enables simultaneous exploration of the morphology and molecular structure of the blends.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Li et al reported that PP components crystallized isothermally are immiscible with HDPE and LDPE and are miscible with LLDPE. 14 The purpose of the present study is to investigate the molecular structure, crystallinity, and morphology of the three kinds of PE/PP blends, HDPE/PP, LLDPE/PP, and MEPE/PP by using Raman spectroscopy, [19][20][21][22][23][24][25] Raman mapping, 26 scanning electron microscopy (SEM), 24,25 WAXD, 23,27 and DSC. 25,27 Raman mapping enables simultaneous exploration of the morphology and molecular structure of the blends.…”
mentioning
confidence: 99%
“…14 The purpose of the present study is to investigate the molecular structure, crystallinity, and morphology of the three kinds of PE/PP blends, HDPE/PP, LLDPE/PP, and MEPE/PP by using Raman spectroscopy, [19][20][21][22][23][24][25] Raman mapping, 26 scanning electron microscopy (SEM), 24,25 WAXD, 23,27 and DSC. 25,27 Raman mapping enables simultaneous exploration of the morphology and molecular structure of the blends. 26,[28][29][30][31] SEM is a well-established method for morphological characterization and supports the Raman mapping results by microscope images.…”
mentioning
confidence: 99%
“…Although there was no direct evidence of the TEM photograph, it has been considered that in the extruded strand, the polymer chains were oriented in the extrusion direction and caused one‐dimensional crystal growth predicted from the Avrami equation. It was reported that oriented crystals were formed in the extruded strand of the blend compound of nylon 12 and HDPE …”
Section: Resultsmentioning
confidence: 99%
“…For example, it was found that adding a compatibilizer to high density polyethylene/polyamide-6 (HDPE/PA6) blends gave higher impact strength where the viscosity ratio between both phases has a strong influence, especially between 0.8 and 1.3. 9,10 Over the years, several studies were published on the relations between morphology and properties of HDPE/PA blends prepared by extrusion, [11][12][13][14][15] injection, 11,[15][16][17] and blow molding. 18.19 On the other hand, foaming polymer blends received less attention, but systems like polyethylene/polypropylene 20 and polypropylene/polystyrene 21 were the most studied.…”
Section: Introductionmentioning
confidence: 99%